Evidences for Red Pigment Concentrating Hormone (RPCH) and Beta-Pigment Dispersing Hormone (β-PDH) Inducing Oocyte Meiotic Maturation in the Chinese Mitten Crab, Eriocheir sinensis - Wei, Ling-Ling; Chen, Tian-Tian; Luo, Bi-Yun; Qiu, Gao-Feng (Frontiers in Endocrinology, 2021)
Red pigment concentrating hormone (RPCH) and pigment dispersing hormone (PDH) are crustacean neuropeptides involved in broad physiological processes including body color changes, circadian rhythm, and ovarian growth. In this study, the full-length cDNA of RPCH and PDH were identified from the brain of the Chinese mitten crab Eriocheir sinensis. The deduced RPCH and PDH mature peptides shared identical sequence to the adipokinetic hormone/RPCH peptides family and the β-PDH isoforms and were designated as Es-RPCH and Es-β-PDH, respectively. Es-RPCH and Es-β-PDH transcripts were distributed in the brain and eyestalks. The positive signals of Es-RPCH and Es-β-PDH were localized in the neuronal clusters 6, 8, 9, 10, and 17 of the brain as revealed by in situ hybridization. The expression level of Es-RPCH and Es-β-PDH mRNA in nervous tissues were all significantly increased at vitellogenic stage, and then decreased at the final meiotic maturation stage. The administrated with synthesized Es-RPCH peptide results in germinal vesicles shift toward the plasma membrane in vitellogenic oocyte, and significant decrease of the gonad-somatic index (GSI) and mean oocyte diameter as well as the expression of vitellogenin mRNA at 30 days post injection in vivo. Similar results were also found when injection of the Es-β-PDH peptide. In vitro culture demonstrated that Es-RPCH and Es-β-PDH induced germinal vesicle breakdown of the late vitellogenic oocytes. Comparative ovarian transcriptome analysis indicated that some reproduction/meiosis-related genes such as cdc2 kinase, cyclin B, 5-HT-R and retinoid-X receptor were significantly upregulated in response to Es-RPCH and Es-β-PDH treatments. Taken together, these results provided the evidence for the inductive effect of Es-RPCH and Es-β-PDH on the oocyte meiotic maturation in E. sinensis.